1994
DOI: 10.1007/bf00198201
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral renal cystic disease in an adult

Abstract: Unilateral renal cystic disease (URCD) is a rare, nonfamilial, nonprogressive, unilateral cystic disorder of the kidney. Very few adults with this condition have been documented [1-4]. We describe a case with a 30 year radiologic follow-up. Absence of a family history of cystic renal disease, benign clinical course through adulthood, and limitation of the process to one kidney distinguish this condition from asymmetric autosomal dominant polycystic kidney disease (ADPKD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Since CT became popular, the surgical confirmation of URCD is no longer needed if patients have characteristic CT findings in combination with genetic and clinical manifestations. 14 Unilateral cystic change of the kidney has been reported in children as an unusual presenting manifestation of ADPKD. 15,16 and has recently been reported to occur in autosomal recessive polycystic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…Since CT became popular, the surgical confirmation of URCD is no longer needed if patients have characteristic CT findings in combination with genetic and clinical manifestations. 14 Unilateral cystic change of the kidney has been reported in children as an unusual presenting manifestation of ADPKD. 15,16 and has recently been reported to occur in autosomal recessive polycystic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of suspect lymph nodes and homogeneous tumor mass as well as the presence of cysts in other areas of the affected kidney in our patient made the diagnosis of cystic nephroma less likely. Unilateral renal cystic disease is a less well known entity reported that is non-familial and non-progressive [1,2]. Segmental multicystic dysplastic kidney disease was unlikely in our patient since on the CT scan there was normal contrast enhancement in the renal tissue adjacent to the cysts and a lack of evidence of duplication of the collecting system.…”
mentioning
confidence: 65%
“…There are no associated cysts in the unaffected kidney or any other intra‐abdominal organ. Some studies have reported small simple cysts in the other kidney 3 . Others have reported the evolution of unilateral disease into bilateral disease after a long‐ term follow up 4 …”
Section: Discussionmentioning
confidence: 99%